Beyond Rebalanced Haemostasis: Haemostatic Phenotypes, Thrombin Generation, and Clinical Risk in Chronic Liver Disease - Sohaib Mukhtar Agouba; Pavla Bradacova; Jan Mikler; Miroslava Drotarova; Kristina Maria Belakova; Monika Brunclikova; Veronika Voskova Gemelova; Jan Stasko; Ingrid Skornova; Tomas Simurda (TH Open, 2026)
Abstract Advanced chronic liver disease (ACLD) profoundly remodels haemostasis through concurrent reductions in procoagulant factors and natural anticoagulants, qualitative platelet abnormalities, elevated von Willebrand factor and factor VIII, and dynamic alterations in fibrinolysis. Although rebalanced haemostasis has transformed understanding of coagulation in cirrhosis, accumulating evidence indicates that haemostatic balance varies according to disease aetiology, fibrosis severity, and clinical stage. This review advances a phenotypic framework for haemostasis in chronic liver disease and explores its implications for risk stratification and antithrombotic management. Three developments support this framework. First, thrombomodulin-modified thrombin generation assays identify distinct haemostatic phenotypes across the disease spectrum, distinguishing the hypercoagulable profile of compensated cirrhosis from hypocoagulable states observed in acute-on-chronic liver failure, whereas metabolic dysfunction–associated steatotic liver disease emerges as a particularly prothrombotic phenotype. Second, recent studies link liver stiffness measurement with thrombin-generation parameters, suggesting convergence between structural liver injury and functional haemostatic assessment. Third, complementary evaluation of fibrin structure, fibrinolysis, plasmin generation, and viscoelastic clot mechanics provides information beyond thrombin kinetics alone, despite important analytical limitations. The review applies this framework to clinically relevant complications, including bleeding, venous thromboembolism, atrial fibrillation, and portal vein thrombosis (PVT). Recent histopathological and clinical evidence challenges the traditional concept of cirrhotic PVT as a manifestation of systemic hypercoagulability and instead supports a predominantly vascular pathogenesis driven by portal-flow abnormalities, endothelial dysfunction, and intimal remodelling. Collectively, these findings support a transition from rebalanced haemostasis towards precision haemostatic phenotyping in ACLD.